Jurnal Penyuluhan: Tingkat Adopsi Inovasi Pengelolaan Tanaman Terpadu (PTT) Padi Sawah di Kecamatan Leuwiliang, Kabupaten Bogor - Ismilaili Ismilaili, Ninuk Purnaningsih, Pang S Asngari (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Integrated crop management (ICM) can increase productivity, economic benefit rice farming through the efficient use of inputs, and conserve land resources for sustainable production systems. The purpose of this study is to analyze the degree of adoption, perception of ICM, and factors that influence the adoption of innovation ICM of paddy in Leuwiliang District. The research location was in Barengkok village and Leuwimekar village, Leuwiliang Sub-district.